Prevalence and risk factors for diabetic neuropathy and painful diabetic neuropathy in primary and secondary healthcare in Qatar. Issue 4 (14th September 2020) - Ponirakis, Georgios; Elhadd, Tarik; Chinnaiyan, Subitha; Hamza, Abdul H; Sheik, Sanaulla; Kalathingal, Mohamed A; Anodiyil, Mohamed S; Dabbous, Zeinab; Siddique, Mashhood A; Almuhannadi, Hamad; Petropoulos, Ioannis N; Khan, Adnan; et al.
Abstract: Aims/Introduction: This study determined the prevalence and risk factors for diabetic peripheral neuropathy (DPN) and painful DPN (pDPN) in patients with type 2 diabetes in primary healthcare (PHC) and secondary healthcare (SHC) in Qatar. Materials and Methods: This was a cross‐sectional multicenter study. Adults with type 2 diabetes were randomly enrolled from four PHC centers and two diabetes centers in SHC in Qatar. Participants underwent assessment of clinical and metabolic parameters, DPN and pDPN. Results: A total of 1, 386 individuals with type 2 diabetes (297 from PHC and 1, 089 from SHC) were recruited. The prevalence of DPN (14.8% vs 23.9%, P = 0.001) and pDPN (18.1% vs 37.5%, P < 0.0001) was significantly lower in PHC compared with SHC, whereas those with DPN at high risk for diabetic foot ulceration (31.8% vs 40.0%, P = 0.3) was comparable. The prevalence of undiagnosed DPN (79.5% vs 82.3%, P = 0.66) was comparably high, but undiagnosed pDPN (24.1% vs 71.5%, P < 0.0001) was lower in PHC compared with SHC. The odds of DPN and pDPN increased with age and diabetes duration, and DPN increased with poor glycemic control, hyperlipidemia and hypertension, whereas pDPN increased with obesity and reduced physical activity. Conclusions: The prevalence of DPN and pDPN in type 2 diabetes is lower in PHC compared with SHC, and is attributed to overall better control of risk factors and referral bias due to patients with poorly managed complications being referred to SHC. However, approximately 80% of patients had not been previously diagnosed with DPN in PHC and SHC. Furthermore, we identified a number of modifiable risk factors for PDN and pDPN. Abstract : The prevalence of diabetic neuropathy and painful diabetic neuropathy is lower in primary healthcare, and is attributed to better control of risk factors for diabetic peripheral neuropathy. However, approximately 80% of patients with diabetic neuropathy were undiagnosed in both primary and secondary healthcare. Diabetic neuropathy is associated with poor glycemic control, hyperlipidemia and hypertension, whereas painful neuropathy is associated with obesity and reduced physical activity.